Establishing proper scanning conditions in atomic force microscopy on polyimide and polyurethane samples and their effect on 3D surface texture parameters. Issue 5 (23rd April 2015) - Stoica, Iuliana; Hitruc, Elena Gabriela; Timpu, Daniel; Barboiu, Virgil; Vasilescu, Dan Sorin
Summary Several atomic force microscopy (AFM) tests have been carried out on both smooth (polyimide) and rough (polyurethane) surfaces so that to obtain the best results; subsequently, the optimization of experiments performed is presented. A special emphasis has been put on the effect of tip geometry, image pre‐processing procedure, scanning area, resolution, pixel size, and cantilever oscillation amplitude in tapping mode, as well as on the quality of the topographical images and 3D surface texture parameters. After viewing the scanning tip and finding out its sharpness, degradation, and contamination, a simultaneous calibration in X, Y, and Z directions, lateral calibration of SPM scanners and detection of lateral non‐linearity, hysteresis, creep, and cross‐coupling effects has been made. We have established the following experimental parameters: proper scanning resolution (512 × 512 pixels), adequate pixel size (between 2.9 and 19.5 nm) and suitable intermittent contact region (moderate tapping) for which the AFM images present good contrast and resolution. Using these parameters, the values of 3D texture parameters remain constant. These kinds of measurements are extremely important to conduct further AFM experiments on polyimide and polyurethane surfaces under optimal conditions, thus avoiding unwanted artifacts on the morphological images or unrealistic values for the 3D surface texture parameters that might occur. SCANNING 37:335–349, 2015. © 2015 Wiley Periodicals, Inc.